Patterns of genetic differentiation among populations of Amrasca biguttula biguttula (Shiraki) (Cicadellidae: Hemiptera). (18th August 2018) - Akmal, Muhammad; Freed, Shoaib; Dietrich, Christopher H.; Mehmood, Mudassir; Razaq, Muhammad
Abstract: Cotton leafhopper, Amrasca biguttula biguttula (Shiraki), a serious sucking insect pest of cotton and vegetables is present throughout South and Southeast Asia. Genetic differentiation within A . biguttula biguttula populations collected from 16 cotton growing areas of Punjab, Pakistan, was examined by sequencing the barcode region of the mitochondrial cytochrome oxidase subunit 1 (COI) gene. The dendrogram obtained by neighbour joining analysis of COI sequences confirmed the presence of single species of cotton leafhopper. The overall average pairwise divergence was 0.01. Very little variation was found among populations from cotton growing areas of Punjab, Pakistan and these were most similar to populations from North India. South Indian populations were grouped together and were generally more divergent. Extensive migration of this pest species among cotton-growing areas in the Indian subcontinent may hinder genetic diversification of cotton leafhopper. Four Pakistani samples of cotton leafhopper tested positive for Wolbachia infection but were not clearly differentiated from non- Wolbachia infected samples, suggesting that Wolbachia did not cause reproductive incompatibilities.